Identification and Biochemical Properties of Two New Acetylcholinesterases in the Pond Wolf Spider (Pardosa pseudoannulata). - Xiangkun Meng; Chunrui Li; Chunli Xiu; Jianhua Zhang; Jingjing Li; Lixin Huang; Yixi Zhang; Zewen Liu (PLoS ONE, 2016)
Acetylcholinesterase (AChE), an important neurotransmitter hydrolase in both invertebrates and vertebrates, is targeted by organophosphorus and carbamate insecticides. In this study, two new AChEs were identified in the pond wolf spider Pardosa pseudoannulata, an important predatory natural enemy of several insect pests. In total, four AChEs were found in P. pseudoannulata (including two AChEs previously identified in our laboratory). The new putative AChEs PpAChE3 and PpAChE4 contain most of the common features of the AChE family, including cysteine residues, choline binding sites, the conserved sequence 'FGESAG' and conserved aromatic residues but with a catalytic triad of 'SDH' rather than 'SEH'. Recombinant enzymes expressed in Sf9 cells showed significant differences in biochemical properties compared to other AChEs, such as the optimal pH, substrate specificity, and catalytic efficiency. Among three test substrates, PpAChE1, PpAChE3 and PpAChE4 showed the highest catalytic efficiency (Vmax/KM) for ATC (acetylthiocholine iodide), with PpAChE3 exhibiting a clear preference for ATC based on the VmaxATC/VmaxBTC ratio. In addition, the four PpAChEs were more sensitive to the AChE-specific inhibitor BW284C51, which acts against ATC hydrolysis, than to the BChE-specific inhibitor ISO-OMPA, which acts against BTC hydrolysis, with at least a 8.5-fold difference in IC50 values for each PpAChE. PpAChE3, PpAChE4, and PpAChE1 were more sensitive than PpAChE2 to the tested Carb insecticides, and PpAChE3 was more sensitive than the other three AChEs to the tested OP insecticides. Based on all the results, two new functional AChEs were identified from P. pseudoannulata. The differences in AChE sequence between this spider and insects enrich our knowledge of invertebrate AChE diversity, and our findings will be helpful for understanding the selectivity of insecticides between insects and natural enemy spiders.